Influence of the SiC matrix introduction time on the microstructure and mechanical properties of Cf/Hf0.5Zr0.5C-SiC ultra-high temperature composites. Issue 3 (1st February 2022) - Liu, Rongjun; Yang, Lingwei; Miao, Huaming; Jiang, Minshu; Wang, Yanfei; Liu, Xingyu; Wan, Fan
Abstract: Cf /Hf0.5 Zr0.5 C-SiC composites were prepared by introducing Hf0.5 Zr0.5 C matrix (11 cycles) and SiC matrix (9 cycles) into the carbon cloth preform through precursor impregnation and pyrolysis (PIP) process. The influence of the introduction time of SiC matrix on the microstructure and mechanical properties of Cf /Hf0.5 Zr0.5 C-SiC composites was studied, and the results show that with the increase of the PIP cycles of the SiC matrix introduced before Hf0.5 Zr0.5 C matrix, the composite open porosity decreased, and the flexural strength and modulus presented an obvious upward trend. CS45 sample, which has 4 cycles of PIP SiC introduced in advance, has the highest flexural strength, flexural modulus and interfacial shear strength of 402.73 ± 35.73 MPa, 56.92 ± 3.97 GPa and 100.88 ± 7.79 MPa, respectively. Hf0.5 Zr0.5 C matrix has a loose and porous structure, so when more SiC matrix was introduced in advance, its covering effect on the surface of fibers led to less intra-bundle pores and thusly denser composite structure, and due to the compactness of SiC matrix, better overall bonding of fiber, interface and matrix was achieved, as well as better load transfer effect, which led to obvious interfacial debonding and cracking based on the in-situ SEM observation during flexural tests. While in the sample without pre-introduced SiC, the cracking occurred mainly between the interface and porous matrix and the overall performance of the material was poor.